Medication-induced upper gastrointestinal tract injury. Issue 2 (24th October 2008) - Chen, Z; Scudiere, J R; Montgomery, E
Abstract : Medication-induced upper gastrointestinal (GI) tract injuries are probably fairly common, yet these injuries are rarely documented in pathology reports. Since these injuries often manifest as non-specific histological changes, making a definitive diagnosis of medication-induced injury can be challenging. Three types of evidence can assist in the establishment of a diagnosis: specific histological patterns, the presence of medication fragments in tissue, and clinical data. Histological patterns may reflect specific tissue responses to medication effects or medication toxicity. Morphological clues of medication use such as pill fragments and crystal deposition may be visible within the tissue itself. Clinical data, including medication history, endoscopic findings, and predisposing conditions can alert the pathologist to situations where medication-induced injury should merit a high ranking on the differential diagnosis list. Except for rare cases where characteristic histological changes can be diagnostic, clinical correlation is essential when diagnosing medication-induced injuries. In this review, key features of the most commonly encountered medication-induced upper GI tract injuries are briefly discussed, and a practical guide to assist the practicing pathologist in the recognition and diagnosis of these injuries is provided.